The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1097/00003246-200005000-00035
|View full text |Cite
|
Sign up to set email alerts
|

The effect of heat on cytokine production in rat endotoxemia

Abstract: Our study demonstrates that heat leads to pulmonary protection of short duration in severe endotoxemia. This protection was not mediated by plasma TNF-alpha, IL-10, or NO. Contrary to our hypothesis, pretreatment with heat increased rather than decreased the plasma MIP-2 concentration and alveolar macrophage production of MIP-2 in endotoxemia. The mechanism of heat-conferred pulmonary protection in endotoxemia remains unclear. Alveolar macrophages do not produce IL-10 in endotoxemia. The increased MIP-2 produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…All other rats were placed in the oven at room temperature for 15 min. We have previously confirmed that HSP 70 inducible was present in the lung tissue and spleen of rats using this method (2).…”
Section: Heat Stresssupporting
confidence: 55%
See 1 more Smart Citation
“…All other rats were placed in the oven at room temperature for 15 min. We have previously confirmed that HSP 70 inducible was present in the lung tissue and spleen of rats using this method (2).…”
Section: Heat Stresssupporting
confidence: 55%
“…Heat stress delivered prior to endotoxemia results in the production of heat shock proteins, which may play a protective role in cardiopulmonary dysfunction (1)(2)(3)(4)(5)(6). Heat shock proteins (HSP) are named based on their molecular weight.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological relevance of 59.4 1C is questionable since this T a is not routinely encountered in nature (Adolph, 1947). Similarly, the majority of these studies exposed animals to pre-heated environmental chambers (Adolph, 1947;DuBose et al, 1983;Gathiram et al, 1987;Heidemann et al, 2000;Hubbard et al, 1977;Ohara et al, 1975;Wright, 1976;Wright et al, 1977), which represents a heat ''shock'' rather than heat ''stress'' paradigm . In vitro studies have also used heat shock paradigms (e.g., 42-43 1C water bath exposure for 1 h) to examine responses in different cell types (D'Souza et al, 1994;Watanabe et al, 1997Watanabe et al, , 1998.…”
Section: The Hyperthermic Response To Heat Exposurementioning
confidence: 99%
“…The ESR spectrum allows the original reactive radical to be identified and quantified. The spectrum of the reaction without muscle was recorded as a control, and a standard curve for SOD activity was constructed based on spectra with known SOD concentrations of 5,10,15,20,25,30,40, and 50 U/ml. The reaction mixture consisted of 50 μl of homogenate, 50 mM phosphoric acid buffer, 2 mM hypoxanthine (6-hydroxypurine), 0.4 U/ml xanthine oxidase, and 20 μl of 9.2 M 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) as a spin trap.…”
Section: Methodsmentioning
confidence: 99%
“…Recent papers have proposed that heat shock proteins (HSPs) can prevent exercise-induced muscle injury and play a role in skeletal muscle recovery and remodeling/adaptation processes after high-force eccentric exercise [7][8][9]. Heat shock preconditioning (HS) has been shown to reduce tissue injury induced by a variety of insults [10][11][12][13], and several investigations in rat skeletal muscle have demonstrated that HS protected muscle from disuse atrophy [14] and from oxidant damage during reloading after immobilization [15].…”
mentioning
confidence: 99%